The existence of Emok Bank in the perspective of law number 10 of 1998 concerning banking - Lestari, Firda; Nurhayati, Ida (Journal of Applied Sciences in Accounting, Finance, and Tax, 2024)
The people of Parakanjaya Village have been using loans from loan sharks or what is known as "Emok Bank" to meet consumer needs because, with their jobs where their income is uncertain, they have not been able to meet their needs or requirements quickly. However, quite a few people also use the services of "Bank Emok" for productive purposes, namely as business capital. This research aims to describe Bank Emok's practices, Bank Emok's operations, and the obstacles faced by the community as Bank Emok customers. The research method used in this research is a descriptive, qualitative approach with a juridical and societal approach. The data collection techniques used in this research consisted of documents and interviews. The research results show that the legal existence of Emok Bank, especially in its operations, distribution, setting interest rates, and payment methods, is not by regulations, especially the Banking Law. However, the Parakanjaya Village community has helped economically.